2022
DOI: 10.3389/fimmu.2022.974648
|View full text |Cite
|
Sign up to set email alerts
|

Th17 cells in primary Sjögren’s syndrome negatively correlate with increased Roseburia and Coprococcus

Abstract: BackgroundDysbiosis of the gut microbiota is closely related to chronic systemic inflammation and autoimmunity, playing an essential role in the pathogenesis of primary Sjögren’s syndrome (pSS). Abnormalities in the proportions of blood T lymphocyte subtype, that is Th17/Treg, were detected in pSS patients. We aimed to determine the associations between gut microbiota and Th17/Treg in pSS.Method98 pSS patients and 105 healthy controls (NC) were enrolled between Dec 1, 2018, and Aug 31, 2019. The baseline infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 54 publications
0
12
1
Order By: Relevance
“…It is generally accepted that the human gut flora consists of about 30 genera and 500 species of bacteria, the microbiota, and that these intestinal players work together to maintain homeostasis in the human gastrointestinal tract (Ling et al, 2022), ensuring the integrity of the epithelial barrier function of the gut and the normal function of various immune cells. Our group has found that dysbiosis of the intestinal flora is associated with many autoimmune diseases, such as primary Sjögren's syndrome (Xin et al, 2022), systemic lupus erythematosus (Yaigoub et al, 2022) and Takayasu arteritis (TA) (Fan et al, 2022). But in this study, our analysis found significantly lower intestinal bacterial abundance and species richness in children with IgAV, KD and IgAN groups than in healthy children, but also a relatively increased number of genera in the different diseases.…”
Section: A B Figurecontrasting
confidence: 66%
“…It is generally accepted that the human gut flora consists of about 30 genera and 500 species of bacteria, the microbiota, and that these intestinal players work together to maintain homeostasis in the human gastrointestinal tract (Ling et al, 2022), ensuring the integrity of the epithelial barrier function of the gut and the normal function of various immune cells. Our group has found that dysbiosis of the intestinal flora is associated with many autoimmune diseases, such as primary Sjögren's syndrome (Xin et al, 2022), systemic lupus erythematosus (Yaigoub et al, 2022) and Takayasu arteritis (TA) (Fan et al, 2022). But in this study, our analysis found significantly lower intestinal bacterial abundance and species richness in children with IgAV, KD and IgAN groups than in healthy children, but also a relatively increased number of genera in the different diseases.…”
Section: A B Figurecontrasting
confidence: 66%
“…The experiment procedures consist of DNA extraction and Illumina sequencing, Operational taxonomic unit (OTU) cluster analysis and species annotation and Bioinformatics analysis, as previously described ( Xin et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the diversity of gut microbiota, we observed that six studies indicate signi cantly lower αdiversity of gut microbiota in patients with primary Sjogren's syndrome compared to the healthy control group [13,28,29,[31][32][33]. Two studies suggested a signi cant difference in α-diversity between the two groups [30,35], while one study indicated a signi cant increase in α-diversity [20].…”
Section: Discrepant Gut Microbiota Diversity Between Primary Sjogren'...mentioning
confidence: 99%
“…The total sample size across all ten studies was 1817 participants, comprising 504 case groups and 1313 control groups. Nine studies included compared discrepancies in gut microbiota between primary Sjogren's syndrome patients and health controls [20][21][22][23][24][25][26][27][28]. Seven of the nine studies included were from China [20, 22-25, 27, 28], while the others were from the Netherlands and Spain[21, 26].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation